2017
DOI: 10.7567/jjap.56.0802a1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization switching schemes for nanoscale three-terminal spintronics devices

Abstract: Utilizing spintronics-based nonvolatile memories in integrated circuits offers a promising approach to realize ultralow-power and high-performance electronics. While two-terminal devices with spin-transfer torque switching have been extensively developed nowadays, there has been a growing interest in devices with a three-terminal structure. Of primary importance for applications is the efficient manipulation of magnetization, corresponding to information writing, in nanoscale devices. Here we review the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 179 publications
0
35
0
Order By: Relevance
“…SOT in the context of electrical writing in magnetic memories (Fukami and Ohno, 2017;Prenat et al, 2016) is the central topic of this review. The technological relevance of the SOT for the development of the next generation of magnetic random access memories (MRAMs) was pointed out in breakthrough reports by Miron et al, 2011a andLiu et al, 2012b, where they demonstrated SOT switching of the recording magnet.…”
Section: Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…SOT in the context of electrical writing in magnetic memories (Fukami and Ohno, 2017;Prenat et al, 2016) is the central topic of this review. The technological relevance of the SOT for the development of the next generation of magnetic random access memories (MRAMs) was pointed out in breakthrough reports by Miron et al, 2011a andLiu et al, 2012b, where they demonstrated SOT switching of the recording magnet.…”
Section: Contentsmentioning
confidence: 99%
“…The out-of-plane writing current geometry of this more technologically mature switching principle sets physical limitations on efficiency and endurance of the STT-MRAM cell. These can be overcome by the in-plane writing current geometry of the SOT (Fukami and Ohno, 2017;Prenat et al, 2016).…”
Section: Figure 3 Flipping the Bitmentioning
confidence: 99%
See 1 more Smart Citation
“…The separate read and write channels in the 3T-MTJ geometry offer additional advantages; faster read-out without read disturbance and lower write energy. While the development of SOT switching has focused primarily on nanoscale perpendicularly magnetized MTJs, their SOT effective-field switching requires much higher currents than can be provided by a reasonably scaled CMOS transistor (current densities in the SH channel are ≥ 1.4 x 10 8 A/cm 2 ) [16], and fast, low write error rate (WER) switching has not yet been demonstrated. Here we report a dramatic performance improvement for in-plane-magnetized 3T-MTJs wherein the strong SOT arising from nano-channels of beta-phase W is combined with two recently discovered effects of Hf atomic layer modifications of the FM-MgO and HM-FM interfaces that, respectively, enhance the interfacial perpendicular magnetic anisotropy energy density [17] and reduce interfacial spin memory loss [18].…”
mentioning
confidence: 99%
“…Thus, we can conclude that through controlling the PMA via electrical field driven oxygen ion migration, the spin‐orbit torque induced magnetization switching can be controlled. Furthermore, the memristive behavior that arises from the SOT‐induced multilevel intermediate states due to partial magnetization switching also provides an attractive method for designing multi‐bit data storage43,44 and neuromorphic computing 45–47…”
Section: Resultsmentioning
confidence: 99%